The Effectiveness of Betel Leaf Water on Perineal Wound Healing among Post-partum Mothers: A Literature Review - Maryati, Ida; Muslim, Revita Nur Istiqomah; Meilani, Intan Lutfi; Mahdhiya, Naifa Zahra; Iriana, Dhiya Ulhaq; Rausanfikra, Syiffa Salsabila (Alta Dharma Publisher, 2023)
Background: Perineal injury is an injury on a urogenital diaphragm or levator ani muscle, which occurs during vaginal delivery and can occur without perineal skin or vagina injury, so it is not visible from the outside. Perineal wound healing can be done pharmacologically and non-pharmacological. Non-pharmacological therapy can be done by using betel leaf water. Objective: This study aims to determine the effectiveness of using betel leaf water in healing perineal wounds in post-partum mothers. Method: This literature review used the PRISMA flow chart 2020 to describe the efficacy of betel leaf water on perineal wound healing in post-partum mothers. Result: A review of eight articles showed that using betel leaf water significantly improved the perineal wound healing process in post-partum women with an average P-Value of <0.05. Conclusion: Giving betel leaf boiled water is effective in healing the perineal wound among post-partum mothers. Recommendation: Betel leaf water can be recommended as one of the interventions in healing perineal wounds post-partum